Confirmation of non N-glycan linked mannose glycosylation in chitinase 42 kDa secreted by Trichoderma harzianum BIO10671 - Mustafa, Muskhazli; Qamaruz Zaman, Faridah; Ramli, Salfarina; Tohfah, Nor Farizan; Ithnin, Nalisha; Wallis, Gregg L. F. (Academic Journals, 2008)
Citinase 42 kDa produced by Trichoderma harzianum has been proven as a prime compund to be excreted onto the hyphae of the pathogen causing localised cell wall lysis at the point of interaction. This finally initiate the process of the host cell becomes empty of cytoplasm, disintegrates and shows a rapid collapse. This study investigates the existence of N-glyan linked mannose in chitinase 42 kDa from T.harzianum BIO10671 was initially purified using anion exchange chromatography prior to a series of experiments such as immunoblotting against the chitinase 42 kDa antibody, lectin staining for detecting any terminal linked mannose and galactofuranose detection to determine the presence of galactofuranose components in glycoproteins. The enzyme purification varvested about 12-fold of chitinase 42 kDa after overnight incubation in chitinase 42 kDa antibody suggesting taht the gene for chitinase 42 kDa was greatly expressed in this strain.There are no intervation of galactofuranose on any of the terminal mannose in chitinase 42 kDa as shown by negative results on samples treated with or without endoglycosidase-H and lectin staining. Therefore, it can be concluded that glycosylation occured in the chitinase 42 kDa from T.harianum 42 kDa was not in the form of N-glycan linked mannose as aspected.